Relationship among parenting behavior, SES, academic achievement and psychosocial functioning in Peruvian children - Manrique Millones, Denisse Lisette; Katholieke Universiteit Leuven (2013)
This study addresses how Negative Parental Control (NPC) and Positive Parenting (PP) are associated with achievement in spelling, arithmetic or reading, socio-economic status (SES) and psychosocial factors such as selfworth (SW) and behavioral problems (BP). The sample is formed by 587 children attending 6th grade of regular primary school and their families living in the urban zones of Metropolitan Lima, Peru. Structural Equation Modeling was used to analyze the hypothesized relations. Four models were built combining parenting dimensions and psychosocial factors. All models showed a good fit. Results showed a strong positive relationship between SES and achievement, and between SES and parenting. Strong associations between psychosocial factors and achievement were found. Implications are discussed about the role of SES on families and achievement but also about the role of parenting in children’s psychosocial functioning.